2018
DOI: 10.1111/obr.12780
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intestinal growth in response to variations in energy supply and demand

Abstract: SummaryThe growth of the intestine requires energy, which is known to be met by catabolism of ingested nutrients. Paradoxically, during whole body energy deficit including calorie restriction, the intestine grows in size. To understand how and why this happens, we reviewed data from several animal models of energetic challenge. These were bariatric surgery, cold exposure, lactation, dietary whey protein intake and calorie restriction. Notably, these challenges all reduced the adipose tissue mass, altered hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 124 publications
(152 reference statements)
0
18
0
Order By: Relevance
“…There is also evidence to suggest that intermittent cold-exposure (from 20°C to 4°C) over a period of days increases weight gain and adiposity and that this is associated with transient, intermittent increases in energy intake [21]. Although other mechanisms such as intestinal growth and increased fatty acid absorption [22] may also play a role the impact of BAT, lipectomy on the response to cold-exposure mirrors our own findings and would suggest a compensatory mechanism for heat production in obesity when adaptive thermogenesis is insufficient. Importantly, an increase of c. 0.5g in BAT and of c. 10g in IWAT cannot account for the c. 41g higher weight gain seen in the cold-exposed animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence to suggest that intermittent cold-exposure (from 20°C to 4°C) over a period of days increases weight gain and adiposity and that this is associated with transient, intermittent increases in energy intake [21]. Although other mechanisms such as intestinal growth and increased fatty acid absorption [22] may also play a role the impact of BAT, lipectomy on the response to cold-exposure mirrors our own findings and would suggest a compensatory mechanism for heat production in obesity when adaptive thermogenesis is insufficient. Importantly, an increase of c. 0.5g in BAT and of c. 10g in IWAT cannot account for the c. 41g higher weight gain seen in the cold-exposed animals.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a plausible mechanism linking the gut to this phenotype which needs to be explored. Cold exposure drives intestinal growth, increased fatty acid absorption and paracellular permeability to nutrients [19, 20]. The efficiency of energy utilisation is also sufficient to maintain core body temperature during acute cold exposure [21].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this phenomenon is complex and still under investigation. One of the explanations is increased metabolism of the white fatty tissue, which induces secretion of a number of mediators (probably including leptin) that stimulate, via hypothalamus, intestine growth and cause increased supply of food (through the sensation of hunger) [23]. Experimental models have also shown that deficits in energy supply ('caloric restriction') lead to intestine growth, both quantitative (increase in organ mass and size) and qualitative (increase in intestinal cell amount) [24].…”
mentioning
confidence: 99%
“…Natural mechanisms of biological compensation such as increased energy expenditure at rest by thermoregulation increased hunger in fasting and intestinal growth modulation are usually expressed in individuals in transition from sedentary to physically active condition, and also from this to physical rigor required by more exhaustive and frequent training routines [51,52,53,54]. Such mechanisms hinder sudden metabolic changes during transition and adaptation stages, so that the general metabolism always tends to be focused on ensuring the maintenance of the homeostatic energy state before routine change, whether of dietary origin or muscle work [51,55,56].…”
Section: Discussionmentioning
confidence: 99%